A coupled Lagrangian-Eulerian framework to model droplet to film interaction with heat transfer - Adeniyi, Akinola A. (2015)
A droplet to film interaction modelling Computational Fluid Dynamics (CFD) technique is presented in this work. The eventual target application is an aeroengine bearing chamber where oil is used to lubricate and cool the bearings and the bearing chamber walls. Inside the chamber, the oil is found as jets/filaments, film and as droplets in the highly rotational environment. Of particular interest in this work is the formation of the continuous film from the droplets. Spray-film is another relevant application with droplets forming film as it cools the wall. In this work, the liquid and gas continua are modelled using an enhanced Volume of Fluid (VoF) technique. The droplets in the core-air are tracked using a Lagrangian framework that treats them as discrete particles and are coupled to the Eulerian VoF film upon impact using source terms. In finite volume CFD techniques, a prohibitively large number of computational cells would be required to describe, in details, the droplet-film impact phenomenon. The proposal here is that finer mesh, sufficient to capture the film physics, is used only close to walls or where film is expected to form. Simple droplet train to complex spray-film setups are used to verify and validate for mass, momentum and energy transfer. The technique was also applied to experimental rigs representative of aeroengine bearing chambers; and as with every CFD problems, the choice of boundary conditions determines the final output. A parametric study of the bearing chamber flows shows that film thickness increases with flow rate. The film thickness increases with a reducing shaft speed for same flow rate. The heat transfer coefficient results show that higher flow rates provide better heat transfer at higher shaft speeds.